PENGARUH PERBEDAAN JARAK TANAM TERHADAP PERTUMBUHAN RUMPUT LAUT (Eucheuma cottonii) HASIL KULTUR JARINGAN DENGAN METODE PATOK DASAR DI PERAIRAN GERUPUK - Muhammad Supiandi; Nunik Cokrowati; Ibadur Rahman (Universitas Mataram, 2020)
This study aims to determine the effect of different plant spacing on the growth of seaweed (Eucheuma cottonii) tissue culture results using the bottom off method. This research uses a completely randomized design (CRD). This research was carried out treatment with different plant spacing tissue culture results. Some references on seaweed cultivation advocated applied planting distance is 25 cm. However, distance it is thought to be too wide due to the size of the Eucheuma cottonii tissue culture yields are smaller (50 g) than conventional seed sizes (100 g).There are 4 treatments, namely P0 with a distance of 25 cm as a control treatment, P1 with a distance of 20 cm, P2 with a distance of 15 cm and P3 with a distance of 10 cm, each with 4 replications with a seedling initial weight of 50 g. Research data were analyzed using analysis of variance or analysis of variance (ANOVA) at 5% significance level with a 95% confidence interval. The highest absolute growth was in the P1 treatment with an average value of 124 g, the highest specific growth rate was in the P1 treatment with an average value of 4.15%/day, and the carrageenan yield showed no significant difference. Observation of carrageenan yields on Eucheuma cottonii showed sequential results in each treatment namely control by 17%, P1 and P2 by 16%, and P3 by 14%. The conclusion of this research is distance planting has a real influence on the growth of seaweed Eucheuma cottonii tissue culture by off bottom method. The best planting distance in thid study is P1 (20 cm).